Braun «Iphigenia in Freedom»: destroyed dialogue - Гура, Наталя Петрівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The article deals with the perception of Iphigenia’s myth by German playwright Volkner Braun. Solving the problem of freedom and the possibility of personality’s self-determination, outstanding writer in his dramatic fragment of verse «Iphigenia in Freedom» (1991) presented his interpretation of the classical plot, where bloody story of the Atrides is closely interwoven with historical events of German’s consolidation. Rejection of holistic plot in favor of fragmentariness of the narration allowed the author to represent his discrepant present-day reality.The liberation of the heroine is happening as a result of the exchange without her participating in the process at all (even with her internal resistance), as she is considered to be dumb. The main part of the work is written in form of stream of consciousness, which is built on delusive inner associations, literary allusions (first of all to Goethe) and ironically reconsidered political slogans. The playwright represents Iphigenia’s liberty between the liberation and the sacrifice, whose destiny is closely connected with world’s history. Thanks to intertextual plays with prototexts, Braun keeps current the problem of legitimacy of compulsive actions in different historical contexts. The author tried to reproduce contemporary perception, his reaction to actual social changes and at the same time reflection on the historical process as a whole. If at the beginning of the work the writer combined the detailed myth's problems with the previous history, which was determined by fate, then further reflected the current development of history, which was close to the requirements of the myth.